Study of Ethnomathematics Exploration of Arul Games Lampung Culture - Indah Cahyaningati; Hafsah Adha Diana (Lembaga Intelektual Muda (LIM) Maluku, 2022)
The purpose of this research is to explore the mathematical concepts that exist in traditional arul games. This research is an exploratory study with an ethnographic approach. Data collection techniques used are observation, interviews and literature studies. The results showed that in traditional games arul found mathematical concepts including the concept of division, fractions, comparison, the revival of two circles, the determination of the center point of the circle, the unit is not standard, half hollow ball, circle, chance, distance, speed and time. The mathematical elements contained in traditional games can be used as learning materials in the classroom so that it is more contextual and a means in preserving local culture.